On the decay of event-files—Way more complex than previously thought. - Frings, Christian; Gholamipourbarogh, Negin; Schmalbrock, Philip; Münchau, Alexander; Beste, Christian (Memory & Cognition, 2026)
Event-files are a central concept in human action control as they integrate perception and action. The basic idea is that event-files comprise internal representations of stimuli, motor programs, and sensory effects of actions that are bound together, maintained for some time, and then ultimately decay. Yet the exact nature of the decay of event-files remains elusive. Most previous studies analyzed the decay only on a very coarse-grained scale typically with only two or three different response–stimulus intervals (RSI). Because available data are inconsistent, the decay function could as yet not be delineated, particularly whether it is linear or resembles a typical forgetting curve. In the present study, we analyzed the decay of event-files using nine different RSIs between 400 ms and 2,000 ms in a large sample (N = 156) of neurotypical participants. If event-file decay mimics the typical forgetting curve, the concept of event-files can be better connected to the memory literature. Using unsupervised cluster analysis, the results showed, however, a more complex pattern. In fact, there were different decay functions across participants with only a subset showing a forgetting curve suggesting that (i) event-file decay functions are modulated by interindividual differences and (ii) that the previously observed power function might be a statistical artifact due to averaging. At least in the time range investigated in this study, event-files decay only for a subset of participants. Possible underlying processes are discussed.